Hadis-Hadis Tentang Riba dan Implementasinya dalam Sistem Perbankan - Muhammad Amar Adly; Heri Firmansyah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
Hadiths Related to Usury (Riba) and Their Use in the Banking SystemHadith is the second source used in the making of legal decision based on Islamic law (istinbath). This paper examines the hadiths related to the issue of usury (riba) from the sanad and matan. The type of the research is thematic, and the approach used is sanad and matan criticism to see the degree of sanad and matan of a hadith so that it can or cannot be used as hujjah (evidence) in the making of legal decision (istinbath). The hadiths regarding the issue of usury found are then selected, and there are four hadiths considered to meet the criteria and representation from a number of the hadiths found. The selection of these hadiths is based on the similarities of the matan although the sanad is different. From the sanad, of the four hadiths, there are only two hadiths examined. From the matan, the overall four hadiths are examined because one hadith and another almost have the same matan. Then, this research develops a study on the contemporary Islamic law issues related to usury issues such as insurance and bank interest even though the hadiths studied and utilized as the focus of this research do not explain the form of a ribawi transaction. In this paper, it is found that the hadiths that discuss the issue of usury are sahih (authentic) from both sanad and matan, so they can be used as a legal basis